IDENTIFICATION OF BIOACTIVE COMPOUNDS FROM SQUID INK (Loligo duvauceli) EXTRACTED WITH DIFFERENT SOLVENTS - Vabellina Nuzul; Mery Sukmiwati; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT Squid ink contains secondary metabolites that function to avoid enemy attacks. Several secondary metabolites can determine the presence of antioxidant activity. Solvents with different polarities can produce different yield values and bioactive compounds. This study aimed to determine the yield value and identify bioactive compounds in L. duvauceli ink extract. The method in this study was explorative and the data were analyzed descriptively. L. duvauceli ink was extracted by the maceration method. The treatments used were solvents with different polarity levels, such as n-hexane, ethyl acetate, and ethanol. The parameters carried out in this study were yield and qualitative secondary bioactive compound testing. The yield of squid ink extracts were 1.69% (n-hexane extract), 2.26% (ethyl acetate extract), and 2.77% (ethanol extract). The bioactive compounds identified in the n-hexane solvent were alkaloids and saponins, alkaloids and steroids in the ethyl acetate extract, and alkaloids and phenolic compounds in the ethanol extract. These compounds are thought to act as antioxidants in L. duvauceli ink.Keywords: bioactive compound, maceration, polarity of solvents, and squid ink